Validation of mobile health technology (mhealth tech) for cardiovascular risk detection - Vinoth Gnana Chellaiyan Devanbu; S. Vijayalakshmi; S.M. Suruliraman (Elsevier, 2023)
Background: Wireless health monitoring device is handy, reduces measurement time and aids in screening and monitoring especially in resource limited settings and remote areas leading to early diagnosis and treatment. Objective of this study was to validate mobile health technology (mhealth tech) in cardiovascular risk detection and to assess Cardiovascular Disease (CVD) risk based on WHO's International Society of Hypertension (ISH) risk score among the study population. Methodology: A Cross-sectional study was carried out in 172 participants. Vital parameters were measured by wireless health monitoring device and traditional methods. Pulse rate and respiratory rate were calculated manually. SPO2, temperature and blood pressure were measured by pulse oximeter, thermometer and sphygmomanometer respectively. ROC curve and Independent T-test were done. Results: Mean difference in time spent measuring vitals manually by traditional method and by wireless health monitoring device was 239.65 (P=<0.001, 95% CI = 232.91 to 246.38). Area under the Receiver Operating Characteristic (ROC) curve for accuracy in diagnosing tachycardia, tachypnoea, hypoxia, hyperthermia, systolic and diastolic hypertension was 0.866 (95% CI (0.745-0.988); p=<0.001), 0.866 (95% CI (0.686-1); p=<0.001), 0.872 (95% CI (0.617-1); p = 0.011), 0.931 (95% CI (0.797-1); p=<0.001), 0.907 (95% CI (0.782-1); p=<0.001), and 0.854 (95% CI (0.651-1); p = 0.002) respectively. Conclusion: Wireless health monitoring devices can be used as a screening and monitoring tool. It is convenient, user-friendly and quickly measures vitals, hence can be used in centres with minimal manpower, health camps and mass screening.